EKSPLORASI ETNOMATEMATIKA PADA MONUMEN KEMERDEKAAN DI ALUN-ALUN PROBOLINGGO - Ayuni; Nuryami (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2024)
Mathematics is the study of interconnected forms, magnitudes, and concepts. The purpose of ethnomathematical exploratory research on the Independence Monument in Probolinggo Square is to explore and understand the relationship between culture and culture in Probolinggo society through analysis of elements in the independence monument, such as design, motifs, and symbolism related to community culture. The approach in this inquire about is subjective, with an accentuation on ethnographic strategies. Whereas the most instrument of this consider is this analyst himself. Besides, information collection in investigate utilizing perception, meet, documentation strategies. The data analysis arrange includes the method of information diminishment, information introduction, and conclusions. Based on the comes about of the examination, it appears a relationship between ethnomathematics and nearby culture. Scientific concepts are not as it were caught on individually but moreover coordinates within the setting of everyday life and social legacy of the individuals of ProbolinggoKeyword: Exploration, Ethnomathematics, Probolinggo Independence Monument